(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to analyze the inpatient treatment characteristics of hypertensive patients at Thu Duc city Hospital in 2024. Material and methods: A retrospective cross-sectional study was conducted on all inpatient admissions with a primary diagnosis of hypertension at Thu Duc city Hospital from January to September 2024. Data were extracted from the hospital management system, including prescribed medications, length of hospital stay, comorbidities, the use of five antihypertensive drug classes, and cost distribution. Results: A total of 359 inpatient episodes for primary HTN were recorded. The length of hospital stay ranged from 1 to 22 days, with most patients hospitalized for 1 to 4 days and receiving 6 to 14 medications per episode. The comorbidity rate was 94.2%, with dyslipidemia (63.7%) and cardiovascular diseases (60.1%) being the most common. Calcium channel blockers, angiotensin II receptor blockers, and beta-blockers were the most frequently prescribed antihypertensive drug classes, with utilization rates of 82.2%, 61.6%, and 47.4%, respectively. Conclusion: Inpatients with hypertension at Thu Duc city Hospital exhibit diverse characteristics, with a high prevalence of comorbidities and extensive medication use. The study’s findings can provide valuable scientific evidence to support the development and improvement of healthcare services for patients at the hospital.